The Role of the University in Environmental Education. The Problem of Particulate Pollution in Poland - Ciepiela, Maciej; Sobczyk, Wiktoria (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2021)
University didactics determines the individual’s place in the educational process as well as provides for a multidirectional continuing education which environmental protection is an important point. This discipline perfectly combines methods of working and scientific research. This paper describes particulates which are produced naturally and by anthropogenic sources. The influence of fossil fuel combustion on atmosphere conditions in a large urban agglomeration is shown. I discuss the causes of the high concentration of particulate matter pollution in Poland, which is tied to city planning and the development of the energy industry as well as the municipal and residential sector. The effects of introducing a ban on burning solid fuels in Krakow are reported.